Predictive Index of The Success of The Elementary School Clean and Healthy Living Behavior (PHBS) Program In The Working Area of the Sikumana Health Center, Kupang City - Denilay Richardo Rambing; Livia Ekayanni Sukamdi (Jurnal Indonesia Sosial Sains, 2025)
diseases, yet its success remains inconsistent, particularly in resource-limited areas like Kupang City, East Nusa Tenggara. This study aimed to compile a predictive index for PHBS success by analyzing student, teacher, school, parental, and health center factors. An observational analytic case-control design was employed, involving 24 elementary schools (12 successful and 12 unsuccessful PHBS cases), with data collected via questionnaires and observation sheets from 242 students, 24 teachers, and health center staff. Logistic regression identified key predictors. Student actions (p=0.014) were the strongest predictor, followed by teacher actions (p=0.020) and school facilities (p=0.022), while parental and health center support showed no significant impact. The predictive index formula confirmed student actions as the dominant factor (OR=19.362, 95% CI:1.093–343.068). The findings underscore the need for targeted student-centered interventions and improved school infrastructure. Future research should validate the index in diverse settings and explore technology-based monitoring tools to enhance PHBS sustainability.